2016
DOI: 10.1007/s10265-016-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen photoproduction in green algae Chlamydomonas reinhardtii sustainable over 2 weeks with the original cell culture without supply of fresh cells nor exchange of the whole culture medium

Abstract: Unicellular green algae Chlamydomonas reinhardtii are known to make hydrogen photoproduction under the anaerobic condition with water molecules as the hydrogen source. Since the hydrogen photoproduction occurs for a cell to circumvent crisis of its survival, it is only temporary. It is a challenge to realize persistent hydrogen production because the cells must withstand stressful conditions to survive with alternation of generations in the cell culture. In this paper, we have found a simple and cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…(a) Photoproduction. Photoproduction of H 2 in aquatic sediments is performed by unicellular algae such as Chlorella fusca (phylum Chlorophyta), Tetradesmus obliquus (formerly Scenedesmus obliquus; phylum Chlorophyta) (72), and Chlamydomonas reinhardtii (73), as well as Cyanobacteria. In soils, several purple nonsulfur bacteria perform photoproduction, including Rhodobacter capsulatus (phylum Proteobacteria) (74) and Rhodopseudomonas rutila (phylum Proteobacteria) (75).…”
Section: Overview Of the H 2 Biogeochemical Cyclementioning
confidence: 99%
“…(a) Photoproduction. Photoproduction of H 2 in aquatic sediments is performed by unicellular algae such as Chlorella fusca (phylum Chlorophyta), Tetradesmus obliquus (formerly Scenedesmus obliquus; phylum Chlorophyta) (72), and Chlamydomonas reinhardtii (73), as well as Cyanobacteria. In soils, several purple nonsulfur bacteria perform photoproduction, including Rhodobacter capsulatus (phylum Proteobacteria) (74) and Rhodopseudomonas rutila (phylum Proteobacteria) (75).…”
Section: Overview Of the H 2 Biogeochemical Cyclementioning
confidence: 99%
“…Regarding media components, the aforementioned S deprivation gives the expected effects only if preceded by a photosynthetic growth phase, providing all of the necessary elements for growth. More recently, alongside this strategy, which envisages separate growth and a deprivation step with several operational issues, a different modality that involves minimal quantities of S to simulate a condition of starvation has also been tested [25,26]. Moreover, particular attention should be paid to the carbon source used: it has been observed that an increase in starch reserves during the phase preceding S deprivation can be crucial in supporting production.…”
Section: The Role Of Growth Parameters In Hydrogen Productionmentioning
confidence: 99%
“…In the academic field, C. reinhardtii plays a significant role as a model organism for studying phototaxis, photosynthesis, and the genetics and physiology of flagellar motility. Research has also been reported on clean energy production, such as hydrogen production [ 26 , 27 , 28 , 29 ], and in statistical studies related to the spatial distribution of cells [ 30 ]. Particularly in temperature-related research, it has been utilized as a model plant system for examining many aspects of the heat stress response [ 31 , 32 ], and more recently, it has been used in studies of cold-induced responses [ 24 ].…”
Section: Introductionmentioning
confidence: 99%